Observation of growth and structure of Kr films physisorbed on Ag(111) and Ag(100) - Aki Tosaka; Taro Mitake; Takashi Miura; Ichiro Arakawa (Физика низких температур, 2003)
The structure and growth of two-dimensional crystals of Kr on Ag(111) and Ag(100) have been investigated by means of ellipsometry and eXtremely-low-current Low Energy Electron Diffraction (XLEED) under the quasi-equilibrium condition. The layering growth of a Kr film was observed up to the third layer by ellipsometry while the crystal geometry by XLEED. Kr overlayer on Ag(100) has two types of alignment. In the predominant alignment, one of the unit vectors aligns with <001> of Ag substrate, while in the other alignment with <011>. Kr–Kr spacing in monolayer on Ag is 10% larger than that of bulk.